2023
DOI: 10.2147/ijgm.s409363
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Patients for Postoperative Myocardial Injury After CME Using Machine Learning: A 10-Year Multicenter Retrospective Study

Abstract: Purpose The occurrence of myocardial injury, a grave complication post complete mesocolic excision (CME), profoundly impacts the immediate and long-term prognosis of patients. The aim of this inquiry was to conceive a machine learning model that can recognize preoperative, intraoperative and postoperative high-risk factors and predict the onset of myocardial injury following CME. Patients and Methods This study included 1198 colon cancer patients, 133 of whom experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have confirmed the application value of ML algorithms in clinical diagnosis and prognosis[ 19 , 20 ]. Moreover, ML algorithms play a crucial role in constructing predictive models, especially in assisting clinical decision-makers to precisely identify high-risk patients and offer timely and accurate treatment, thereby enhancing patient prognosis[ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the application value of ML algorithms in clinical diagnosis and prognosis[ 19 , 20 ]. Moreover, ML algorithms play a crucial role in constructing predictive models, especially in assisting clinical decision-makers to precisely identify high-risk patients and offer timely and accurate treatment, thereby enhancing patient prognosis[ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%